ANALISIS KINERJA BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) DALAM PENANGGULANGAN BENCANA TANAH LONGSOR DI KABUPATEN WONOSOBO - Vicki Indra Prastiyono; Maesaroh Maesaroh; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
[This research aims to analyze how the performance of BPBD in overcoming landslide at Wonosobo District and to find out the factors that become the constraints on the BPBD's non optimal performance in overcoming landslide at Wonosobo District. This research is a qualitative descriptive by using purposive sampling to determine the performance of BPBD in overcoming landslide at Wonosobo District. Data collection techniques used in this research are through interview techniques, observation, and documentation. The data obtained were analyzed descriptively through the stages of data inventory, data reduction, data presentation, and conclusion drawing. The results showed that : BPBD's performance in overcoming landslide at Wonosobo district has not been running well because several obstacles are still encountered in several aspects such as productivity, service quality, and responsiveness. Factors causing the non optimal performance of BPBD in overcoming landslides include the lack of supporting equipment for landslide disaster management activities, limited human resources, and the slow pace recovery or rehabilitation of areas affected by disasters.